Identificação dos membros da família das teneurinas em órgãos de primatas não-humanos e roedores - Guiati, Isabella Zacarin [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Teneurins are transmembrane proteins constituted by four homologous (TEN1-4) that are expressed preferentially in the central nervous system, during neurogenesis in invertebrates and vertebrates. However, studies on TEN expressions in non-neuronal tissue and organs are scarce and restricted to genic and protein databases, without detailed analysis. The purpose of the present study was to analyze and compare the distribution of TEN family members in tissues and organs of non-human primates (Sapajus apella) and adult rodents by immunohistochemical technique. In addition, genic expression analysis was performed in some organs to confirm the immunohistochemical data. The main results showed that several cell types are immunoreactive to TENs in all analyzed systems (endocrine, digestive, urinary, circulatory, reproductive and respiratory). This immunoreactivity was not restricted to cell membrane, but it was homogenously distributed in the cell cytosol. TEN3 immunoreactivity was the most interesting, as it was similar to a neuroendocrine peptidergic sytem, exhibiting immunoreactive cells in the adrenal medulla, neuroendocrine cells from epithelium layer of the digestive tract, thyroid parafollicular cells, adenohypophysis, myenteric and submucosal plexuses of digestive tract in rats and non-human primates. TEN3 immunoreactivity was present in the cell membrane only in the respiratory tract. TEN1 immunoreactivity was homogenous in islet of Langerhans and punctiform in acinar cells of the exocrine pancreas. TEN1 immunoreactivity was restricted to certain domains of the cell membrane in the epithelium layer of respiratory and digestive tracts. TEN2 and TEN4 immunoreactivities were more discrete, with interesting data for TEN2 immunoreactivity present in cell membrane of respiratory, urinary and distal part of the...

As teneurinas (TENs) são compostas por quatro membros (teneurina 1 a 4) e foram descritas inicialmente em mamíferos. Esta família de proteínas apresenta expressão preferencialmente no sistema nervoso central e está conservada ao longo das espécies. Basicamente, as teneurinas são expressas principalmente durante a morfogênese em diferentes órgãos e tecidos, em especial durante a neurogênese. O objetivo do presente trabalho foi analisar e comparar a distribuição dos membros da família das TENs em tecidos e órgãos de roedores e primatas não-humanos (Sapajus apella) adultos, através da técnica de imuno-histoquímica, sendo que, a expressão gênica em alguns órgãos foi confirmada através do método convencional de RT-PCR. Os principais resultados mostraram que inúmeros tipos celulares apresentaram imunorreatividade a TENS em todos os sistemas estudados (endócrino, digestório, respiratório, circulatório, urinário e reprodutor). A imunorreatividade as TENs não estava restrita apenas a membrana celular, mas também mostrou distribuição homogênea em todo o citosol. A imunorreatividade a TEN3 mostrou-se conspícua, similar a um sistema peptidérgico neuroendócrino, sendo notadas células imunorreativas na região medular da adrenal, células neuroendócrinas do estomago e intestino, células parafoliculares da tireoide, adeno-hipófise, plexos mioentérico e submucoso do sistema digestório tanto em ratos como na espécie Sapajus, com exceção da marcação na membrana plasmática do sistema respiratório. A imunorreatividade a TEN1 mostrou-se homogênea nas células das ilhotas de Langerhans do pâncreas e punctiforme no citosol das celulas acinares do mesmo; enquanto, esta imunorreatividade mostrou-se restrita a determinados domínios das membranas plasmáticas das células do sistema respiratório e na região do centro...
Keywords: Ratos; Imunohistoquímica; Expressão gênica; Rats